Resistance Switching Memory Devices based on Zinc Oxide Nanoparticles on Paper Substrates - Franco, Miguel Alexandre Martins (2017)
This work reports the development of resistive random access memory (RRAM) on paper using printed Zinc Oxide (ZnO) nanoparticles (NPs) as active layer. RRAM is a novel technology having attracted increasing attention due to their high-speed operation, high-density storage, and low voltage. Most important, due to its characteristics it could replace flash technology which suffers from low endurance, low write speed, and high voltages required for the write operations. Screen printing was chosen because of its versatility in terms of ink viscosity, which is compatible with inks that require low annealing temperatures. The architecture adopted consists in a mixture of ZnO NPs and ethyl cellulose (EC), used as binder, between electron beam evaporated platinum bottom electrode and screen-printed carbon or silver top electrode. The resistive memory device can be programed in bipolar for at most 20 cycles. The retention time of the bipolar switching for both on/off states is reached up to 10 Ks. The operating voltages of SET and RESET is high ~ 20 V and - 10 V respectively. A transition between bipolar switching to unipolar is observed. It is suggested that an instable bipolar resistive switching is due to growth of filaments during cycles. The required voltages for on/off states fluctuate in the range of ~ 5 V which is a strong evidence of non-consistent bipolar resistive switching.